PSIKOLOGI: KEMAMPUAN KOGNITIF DAN SOSIAL-EMOSIONAL PADA ANAK USIA REMAJA AKHIR - Khaldun, Rendra (Jurusan Bimbingan dan Konseling Islam Fakultas Dakwah dan Komunikasi IAIN Mataram, 2013)
Discussion about psychology is very interest because psychology talked about mental and adolescence habit. Besides that, adolescence psychologies were beginner of intelligence, creativity, logic, and smart. The aims of this study were: 1.) to know what cognitive ability had by adolescence. 2.) To know what social emotional that had by adolescence. The method that used in this study was quantitative method. Techniques of collecting data in this study were questionnaire, interview, and documentation. The data analysis based on criterion of data. After the data collecting based on group, the data directlyanalysis based on groups.The results of this study were: 1.) Adolescence ability to thinks was beggin developed and adolescence realize their ability to look at the problems and to looking for solution. 2.) Adolescence beggin given score in look at the problems that related their society such as politic, humanity, and social problems. 3.) adolescence beggin thinks creatively and be able to analysis problems and to looking for the solution.